2021
DOI: 10.3389/fpsyg.2020.537706
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Traits Do Not Predict Functional Family Therapy Outcomes for Adolescents With Behavior Problems

Abstract: Despite the availability of evidence-based treatment models for adolescent behavior problems, little is known about the effectiveness of these programs for adolescents with callous-unemotional (CU) traits. Defined by lack of empathy, lack of guilt, flattened affect and lack of caring, CU traits have been linked to long-term anti-social behavior and unfavorable treatment outcomes and might be negatively related to outcomes in evidence-based programs such as Functional Family Therapy (FFT). This study used a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…The clinical meaningfulness of such statistically significant findings needs to be assessed, as the observed average reduction in our study of a couple of scale points can occur by a minimal 1-scale-point change on merely two or three questions on the ICU12. Furthermore, it seems that baseline levels of CU traits might be a moderator of CU change, as our results, and those of a previous study, observed more pronounced reductions in CU traits for adolescents with elevated baseline levels of CU traits (Thøgersen et al, 2021). Importantly, the growth curve analysis indicate that these reductions might be temporary, and the observed short-term effects could be driven by regression to the mean effects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The clinical meaningfulness of such statistically significant findings needs to be assessed, as the observed average reduction in our study of a couple of scale points can occur by a minimal 1-scale-point change on merely two or three questions on the ICU12. Furthermore, it seems that baseline levels of CU traits might be a moderator of CU change, as our results, and those of a previous study, observed more pronounced reductions in CU traits for adolescents with elevated baseline levels of CU traits (Thøgersen et al, 2021). Importantly, the growth curve analysis indicate that these reductions might be temporary, and the observed short-term effects could be driven by regression to the mean effects.…”
Section: Discussionsupporting
confidence: 80%
“…This implies that FFT provided neither better nor worse outcomes for adolescents with CU traits when compared to the alternative treatments available in Norway. Although there might be plausible theoretical advantages of using the FFT approach to work with youth with CU traits (Thøgersen et al, 2021;White et al, 2013), these were not empirically observed in the current study when FFT was compared to other high-quality treatment options. This might be due to the fact that some of the treatments provided in the control condition (e.g., MST and parent management training) have treatment foci and interventions similar to that of FFT.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of a Danish pre-post treatment study showed that even though CU traits were associated with more rule-breaking behaviour and hyperactivity at the start of treatment, this did not increase the risk of adolescents interrupting or gaining less benefit from FFT [ 67 ]. On the other hand, CU traits were related to the level of improvement as rated by parents, adolescents, and the therapist at the end of treatment.…”
Section: Treatment Of Adolescents With Cumentioning
confidence: 99%